Measuring climate security: Are peaceful countries immune to climate-related security threats? - Madurga Lopez, Ignacio M.; Caroli, Giulia; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2021)
It is widely recognized that climate change has the potential to affect the social, economic, and political processes that can lead to instability, insecurity, and even conflict. These effects are particularly severe in fragile states highly dependent on a climate-sensitive agricultural sector and marked by weak governance. Still, too little is known about which countries and contexts are most likely affected by climate-driven instability and how best to tackle the root causes and predict future crises. We now must fill this gap and develop analytical and support tools that look at climate and conflict risks and how they interact in a systemic and integrated manner. As a key priority, this involves measurements and indicators sensitive to climate-related security risks.